Straf eller behandling: – faktorer af betydning for en stigende anvendelse af psykiatriske særforanstaltninger til ikke-sindssyge lovovertrædere i Danmark i perioden 2003-2013. - Brandt-Christensen, Mette; Ahle, Gitte; Gram Larsen, Tina; Nitschke, Kirsten; Ibsen, Michael (Nordisk Tidsskrift for Kriminalvidenskab, 2021)
Abstract The number of forensic psychiatric patients has steadily increased in many countries during the past 30 years. This increase has been especially pronounced in Denmark when viewed on a per capita basis. Explanations that consider the diversity of possible factors influencing the development are currently insufficient. Most forensic psychiatric patients suffer from psychotic conditions and are convicted under Section 16 of the Danish Penal Code. A smaller proportion is comprised of non-psychotic mentally-disordered offenders convicted under Section 69. In recent years, a hitherto unobserved increase has been seen in the use of treatment sanctions for the latter group. This article describes factors that may have contributed to this development during the period 2003-2013. This is a retrospective file-based study using comparative statistical analysis. The study utilizes 1,078 forensic psychiatric assessment reports concerning non-psychotic mentally-disordered offenders covering the years 2003, 2008, and 2013, together with statements from the Medico-Legal Council and all final verdicts. Results indicate a near doubling in the number of psychiatric sanctions given to non-psychotic mentally-disordered offenders. The total number of forensic psychiatric assessments required by the judicial authorities also increased, though not to the same extent. Geographical differences were found in, among other factors, requests from the police for forensic psychiatric assessments, psychiatric diagnoses and medical recommendations for the court. Interestingly, a significant decrease in the involvement of the Medico-Legal Council occurred during the 10-year study period.